Contribution of the qPCR for the Diagnosis of Pneumocystosis. (4th October 2017) - Issa, Nahema; Gabriel, Frederic; Baulier, Gildas; Accoceberry, Isabelle; Mourissoux, Gaelle; Guisset, Olivier; Camou, Fabrice
Abstract: Background: Pneumocystis jirovecii pneumonia (PCP) is an opportunistic fungal respiratory infection. The incidence of PCP has decreased among HIV patients, however among non HIV-negative patients on immunosuppressive drugs; an increase in incidence is noted. In this population, the diagnosis of PCP is difficult because the clinical presentation is atypical and the direct examination (DE) of the respiratory secretions is often negative. In this context, detection of Pneumocystis jirovecii DNA in respiratory secretions by real-time quantitative chain reaction (qPCR) should be usefull. Methods: In order to evaluate the usefulness of qPCR, all patients hospitalized in medicine or intensive care unit (ICU) in a university hospital and having a positive qPCR in respiratory secretions were included in a retrospective study conducted between 2013 and 2016. Based on clinical data, respiratory secretions, imaging and treatment, patients were classified into three groups: certain PCP, possible, or colonization, irrespective of the value of qPCR. Results: One hundred and fifty patients, including 38 infected with HIV, were included: 75 in medicine and 75 in intensive care. Ninety patients (60%) had bronchoalveolar lavage. The diagnosis of PCP was considered certain or possible for 52 and 77 patients respectively and rejected (colonization) for 21 patients. DE was negative for 78% of non-HIV patients and 29% of HIV patients. Among the 129 patients with PCP, the hospital mortality was 35.9% in ICU and 21.5% in medicine. The median value of qPCR was 76, 650 copies/mL among patients with PCP and 3, 220 copies/mL among colonized patients ( P < 0.001) with no significant difference in type of respiratory specimen or place of hospitalization. The optimal threshold value of qPCR determined from the ROC curve was 10, 100 copies/mL with a sensitivity of 76.6% and a specificity of 86%. Specificity was 100% at the threshold of 59, 250 copies/mL. Conclusion: If qPCR alone is imperfect for the differential diagnosis between colonization and infection, it has the merit of guiding the clinician towards the diagnosis of PCP especially for non-HIV patients whose DE of the respiratory secretions is negative in nearly 80% of cases, both in medicine and ICU. Disclosures: All authors: No reported disclosures.